An orally administered butyrate‐releasing derivative reduces neutrophil recruitment and inflammation in dextran sulphate sodium‐induced murine colitis. (3rd November 2016) - Simeoli, Raffaele; Mattace Raso, Giuseppina; Pirozzi, Claudio; Lama, Adriano; Santoro, Anna; Russo, Roberto; Montero‐Melendez, Trinidad; Berni Canani, Roberto; Calignano, Antonio; Perretti, Mauro; Meli, Rosaria
Abstract : Background and Purpose: Butyrate has shown benefits in inflammatory bowel diseases. However, it is not often administered orally because of its rancid smell and unpleasant taste. The efficacy of a more palatable butyrate‐releasing derivative, N‐(1‐carbamoyl‐2‐phenylethyl) butyramide (FBA), was evaluated in a mouse model of colitis induced by dextran sodium sulphate (DSS). Experimental Approach: Male 10 week‐old BALB/c mice received DSS (2.5%) in drinking water (for 5 days) followed by DSS‐free water for 7 days (DSS group). Oral FBA administration (42.5 mg·kg −1 ) was started 7 days before DSS as preventive (P‐FBA), or 2 days after DSS as therapeutic (T‐FBA); both treatments lasted 19 days. One DSS‐untreated group received only tap water (CON). Key Results: FBA treatments reduced colitis symptoms and colon damage. P‐FBA and T‐FBA significantly decreased polymorphonuclear cell infiltration score compared with the DSS group. FBA reversed the imbalance between pro‐ and anti‐inflammatory cytokines (reducing inducible NOS protein expression, CCL2 and IL‐6 transcripts in colon and increasing TGFβ and IL‐10). Morever, P‐FBA and T‐FBA limited neutrophil recruitment (by expression and localization of the neutrophil granule protease Ly‐6G), restored deficiency of the butyrate transporter and improved intestinal epithelial integrity, preventing tight‐junction impairment (zonulin‐1 and occludin). FBA, similar to its parental compound sodium butyrate, inhibited histone deacetylase‐9 and restored H3 histone acetylation, exerting an anti‐inflammatory effect through NF‐κB inhibition and the up‐regulation of PPARγ. Conclusions and Implications: FBA reduces inflammatory intestinal damage in mice indicating its potential as a postbiotic derivative without the problems associated with the oral administration of sodium butyrate. Linked Articles: This article is part of a themed section on Principles of Pharmacological Research of Nutraceuticals. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v174.11/issuetoc